DESCRIBING THE RESULTS OF IMPROVING STUDENT LEARNING THROUGH THE APPLICATION OF THE SNOWBALL THROWING METHOD IN FIKIH SUBJECTS - Lestari, Putri (ANDRAGOGI, 2023)
Learning is often carried out ineffectively due to a number of problems that occur. Inappropriate learning methods are also a problem and will affect students' academic scores. This research was carried out because it was motivated by issues or problems, such as the fact that students are still passive rather than active, that some students still feel embarrassed to ask, and that the lack of enthusiasm for student learning is caused by inaccurate techniques or teacher teaching methods and causes small grades and student learning outcomes. Because of this, researchers are trying to apply the snowball throwing method. The purpose of this study is to improve student learning outcomes. Quantitative methods were used in this study by providing a pre-test and a post-test. The research location is in MTsN 1, Bengkalis. Researchers analyzed the research data using the Wilcoxon test and obtained a Wilcoxon test result of 0.000. The terms of this test are Sig. > 0.05 = 0.000 > 0.05, which means that H0 is rejected and H1 is approved. In this case, the conclusion is that the snowball throwing method can improve student learning outcomes in class VII fikih subjects at MTsN 1 Bengkalis.